2020
DOI: 10.3390/su12072599
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Biochar-Silty Clay Interaction Using In-House Fabricated Cyclic Loading Apparatus: A Case Study of Coastal Clay and Novel Peach Biochar from the Qingdao Region of China

Abstract: Biochar has been recently investigated as an eco-friendly material in bio-engineered slopes/landfill covers. A majority of recent studies have focused on analyzing water retention behavior while very few have examined dynamic behavior (i.e., cyclic loading due to earthquake, wind, or wave) of biochar amended soil. As far as the authors are aware, there is no study on the dynamic behavior of biochar amended soils. Considering the above mentioned study as a major objective, field excavated soil was collected and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The reduced tensile strength of SBC was attributed to the weakening of inter-particle bonding that diminished the density and overall cohesiveness of SBC (Busscher et al., 2011; Chan et al., 2007; Zong et al., 2016). Liu et al. (2020) reported that shear modulus and residual cyclic strength values of SBC with 5%, 10% and 15% BC by weight diminished after 15 cycles during cyclic loading owing to high pore-water pressure development.…”
Section: Resultsmentioning
confidence: 99%
“…The reduced tensile strength of SBC was attributed to the weakening of inter-particle bonding that diminished the density and overall cohesiveness of SBC (Busscher et al., 2011; Chan et al., 2007; Zong et al., 2016). Liu et al. (2020) reported that shear modulus and residual cyclic strength values of SBC with 5%, 10% and 15% BC by weight diminished after 15 cycles during cyclic loading owing to high pore-water pressure development.…”
Section: Resultsmentioning
confidence: 99%
“…Slow pyrolysis was adopted, where the wastes were incinerated in the absence of oxygen at a temperature of 400°C for 3 h. Crystals of biochar were then crushed into powder. Liu et al (2020) found that the addition of this biochar resulted in a decrease in the void ratio, facilitating an interlocking mechanism between the biochar and soil and thus enhancing the dynamic strength.…”
Section: Methodsmentioning
confidence: 99%
“…Using additives such as biochar (Yu et al 2013;Liu et al 2020), microorganism (Preston et al 2001, DeCarlo andCaylor 2019), and fibre (Xu et al 2021) is one of the possible method to increase the strength of soils and resistance to cracking. When fibre added evenly in the soil mass, the tensile strength of fibre can be attached to it when soil is under stressed, thus, enhancing the mechanical properties of the soil mass (Ghiassian et al 2008).…”
Section: Introductionmentioning
confidence: 99%